Unilateral ectopic breast tissue on vulva in postpartum woman: A case report. Issue 6 (February 2018) - Baradwan, Saeed; Wadi, Khalid Al
Abstract: Rationale: Ectopic mammary gland tissues occur in about 2% to 6% of women in general population. Vulva is considered a rare site for the ectopic breast tissue. Patient concerns: We report a rare case of a 27 year-old woman, para 2 and presenting as a vulvar mass in the postpartum period. Diagnoses: Ectopic mammary tissue in vulva. Interventions: The mass was removed by wide local excision. Histopathological assessment revealed features of ectopic mammary tissue Conclusion: The vulvar region is one of the reported sites for ectopic breast tissue in the body. The presence of a rapidly enlarging, well-encapsulated mass in the vulvar region associated with recent delivery or lactation is suggestive of ectopic breast tissue. Lessons: It is important for clinicians to get a good history and consider ectopic breast tissue on vulva in postpartum women and confirm diagnosis via biopsy with histopathological examination.